2016
DOI: 10.1002/rra.3015
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment Sources of Channel and Blue Catfishes Inhabiting the Middle Mississippi River

Abstract: Insight into environments that contribute recruits to adult fish stocks in riverine systems is vital for effective population management and conservation. Catfish are an important recreational species in the Mississippi River and are commercially harvested. However, contributions of main channel and tributary habitats to catfish recruitment in large rivers are unknown. Stable isotope and trace elemental signatures in otoliths are useful for determining environmental history of fishes in a variety of aquatic sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
56
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(64 citation statements)
references
References 27 publications
3
56
0
5
Order By: Relevance
“…These variations in habitat use between the upper Mississippi and the MMR may be due to the pooled nature of the upper Mississippi River, where locks and dams have altered discharge regimes and the distribution of desirable mesohabitats by influencing the large‐scale river features (Phelps et al., ). Laughlin, Whitledge, Oliver and Rude () studying recruitment sources of Mississippi River blue catfish documented that the majority of recruits originated within the Mississippi and Missouri rivers rather than tributaries, further illustrating the importance of main channel habitats.…”
Section: Discussionmentioning
confidence: 99%
“…These variations in habitat use between the upper Mississippi and the MMR may be due to the pooled nature of the upper Mississippi River, where locks and dams have altered discharge regimes and the distribution of desirable mesohabitats by influencing the large‐scale river features (Phelps et al., ). Laughlin, Whitledge, Oliver and Rude () studying recruitment sources of Mississippi River blue catfish documented that the majority of recruits originated within the Mississippi and Missouri rivers rather than tributaries, further illustrating the importance of main channel habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding patterns of movement and habitat use by fishes to fulfil life‐history requirements (including movement between rivers and tributaries) is key for assessing population dynamics and effects of riverscape fragmentation and for conservation of habitats that contribute to population persistence (Fausch, Torgersen, Baxter & Li, ; Schlosser, ). Furthermore, knowledge of spatial patterns in population demographics and fish movement and dispersal patterns in river–tributary networks is important for identifying relevant spatial scales for population assessment and management (Cooke et al., ; Laughlin, Whitledge, Oliver & Rude, ; Porreca et al., ). In many large rivers, channel geomorphology and hydrology have been severely altered through anthropogenic activities such as impoundments, channelisation and bank stabilisation (Nilsson, Reidy, Dynesius & Revenga, ), which has led to global declines in many riverine fish species (Rinne, Hughes & Calamusso, ).…”
Section: Introductionmentioning
confidence: 99%
“…Tributaries may be particularly important as recruitment sources for fishes and sustaining species richness in large, mainstem rivers through fish movement from tributary to main‐stem habitats (Pracheil, McIntyre & Lyons, ; Pracheil, Pegg & Mestl, ). Although tributaries can contribute substantially to recruitment of riverine fish stocks, the extent to which early life‐stage dispersal and movement of older juvenile and adult fishes result in exchange of individuals among main‐stem river and tributary habitats can vary considerably among river–tributary networks and species (Benjamin, Wetzel, Martens, Larsen & Connolly, ; Humston, Priest, Hamilton & Bugas, ; Humston et al., ; Laughlin et al., ; Pracheil et al., ; Sousa, Humston & Freitas, ; Spurgeon, Pegg & Halden, ). Thus, additional studies investigating the exchange of fishes among tributary and main‐stem environments across river systems and among fish species are needed to broaden understanding of the influence of river–tributary connectivity on fish population dynamics and to inform spatially explicit assessment and management of fish populations tailored to particular species and systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laughlin et al . () found that differences in δ 18 O and Sr:Ca persisted over an 8‐year period in the Middle Missouri River, USA. If isotope signatures are more constant than microelemental signatures, then they may provide some advantage in tracing life history of fishes or could be used in conjunction with those microelemental signatures.…”
Section: Discussionmentioning
confidence: 98%